Current Trends in Feeding and Nutrition of Zoo Animals: A review - Das, Asit (Indian Journal of Animal Nutrition, 2018)
Concerned with the declined population of many native species India, considerable attention has been paid on ex- and in situ conservation of endangered species. It is imperative to say that no ex-situ conservation programme would meet success until adequate and balanced nutrition is provided to the animals. However, only limited information is available on nutrition and feeding of wild animals in captivity. An attempt has been made through this review to comprehensively analyze all information related to feeding and nutrition of captive animals so as to formulate diet schedule for different species of captive animals with an ultimate aim of improved reproduction, longevity, health and welfare of zoo-housed animals. Feeding of excessive concentrates may lead to acidosis, laminitis and obesity. Hence, the amount of concentrates should contribute no more than 25-30% of the total calorie requirement of the zoo-housed herbivores. Captive carnivores are also susceptible to obesity and related health problems. Hence, their diet should be restricted according to their body weight. There are certain reports which indicate that feeding of prebiotics and exogenous antioxidant may improve immune staus and the ability of zoo-housed animals to combat stress. Future research should focus on to develop nutritional strategies that would improve reproductive performance, health and welfare of the zoo-housed animals